KERAGAMAN GENDER DEWAN DIREKSI MEMODERASI PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN (Studi Kasus pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Muhammad Akbar; Agung Juliarto (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the effect of disclosure of corporate social responsibility on financial performance, as well as gender diversity of the board of directors as a moderating variable. The CSR disclosure variable is calculated using the ESG disclosure score issued by Bloomberg, the financial performance variable is calculated using return on assets (ROA), and the board of directors' gender diversity variable is calculated using Blau's heterogeneity index. The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) and the Bloomberg database during 2018-2021. The sample in this study was taken using a purposive sampling method which resulted in 59 sample companies to be studied. Data analysis was performed using Partial Least Square (PLS). This study successfully proves that CSR disclosure has a significant effect on financial performance, and proves that gender diversity of the board of directors can strengthen the influence of CSR disclosure on financial performance.